Review of Industry 4.0 in the Light of Sociotechnical System Theory and Competence-Based View : A Future Research Agenda for the Evolute Approach - Imran, Faisal; Kantola, Jussi (Springer, 2019)
This paper reviews the concept of Industry 4.0 related challenges and basic requirements for successful implementation of it. It proposed that sociotechnical system theory (STS) and competence-based view (CBV) are best approaches towards implementation of industry 4.0 in the organizations. STS theory leads to such systems, which are more acceptable to end users and deliver better value. While competence-based view prepares those users to interact efficiently with new systems. To support competence-based view for industry 4.0 we argue that competence models of the Evolute approach need to be revised and updated, as well as, there is need for new competence models for emerging new job profiles. The combination of these three approaches will result into successful implementation of new industry 4.0 systems in the organizations.
Keywords: competence models; evolute competence-based view; industry 4.0; sociotechnical systems; theory; fi=Tuotantotalous|en=Industrial Management|